The Future of Audiences
XXI, 309 p. 3 illus. in color.
Keywords: “Many fear that the algorithmic turn in journalism and cultural production generally evacuates the site of the audience. But, as Das and Ytre-Arne make clear in this skilfully edited volume that distils the research of 22 young European researchers, the audience is still there and we need to listen to them. This fresh and lively book offers many insights into those ordinary things we do as we interact with platforms, while keeping a close eye on the bigger issues: literacy and engagement, the politics of platforms and the elusive possibility of a European public sphere. An exciting read!” –Nick Couldry, Professor, London School of Economics and Political Science, UK “This book sets an agenda for rethinking audience activity in a digital, 'datafied' world. Truly interdisciplinary and collaborative, the interwoven contributions provide innovative theoretical and methodological tools with which to explore audience practices inan increasingly fluid future.” –S. Elizabeth Bird, Professor, University of South Florida, USA “Audience research is now more important than ever, as audiences have become more central to online media dynamics and data flows. With the emerging Internet of Things and the ubiquitous presence of platforms in our lives, this collection offers a timely and important guide to the future of audiences and audience studies. A thorough and insightful foresight study that is indispensable for the next generation of media scholars.” –José van Dijck, Distinguished University Professor, Utrecht University, Netherlands, author of The Culture of Connectivity This book brings together contributions from scholars across Europe to present findings from a foresight analysis exercise on audiences and audience analysis, looking towards an increasingly datafied world and anticipating the ubiquity of the internet of things. The book uses knowledge emerging out of three foresight exercises, produced in co-operation with more than 50 stake-holding organisations and building on systematic reviews of audience research. It works through these exercises to arrive at a renewed agenda for audience studies within communication scholarship in the context of intrusive and connected interfaces and emerging communicative practices. .